Participatory approaches to the conservation and use of plant genetic resources - Friis-Hansen, Esbern; Sthapit, B.; International Plant Genetic Resources Institute (2000)
This technical bulletin reviews and synthesises participatory approaches and tools that are used when working with farmers and local communities in the conservation and use of plant genetic resources. It focuses on practical experiences of traditional farming communities in Asia, Africa and Latin America. The authors of the chapters are leading experts in the field representing community based organisations, NGOs, universities and agricultural research centres. This practical guide is organised in five sections. The first reviews cross-cutting issues such as gender, tools and techniques, and the role of institutions. The second covers farmers' access to genetic resources held ex situ. The third examines local plant genetic resources management and participatory crop improvement. The fourth section looks at community seed banks and local seed systems. The concluding section reviews factors that contribute to supportive policies and public awareness of local people's role in the conservation and use of agrobiodiversity. The book also contains a glossary of terms used in participatory work on plant genetic resources, and a comprehensive bibliography of important publications in this field.